Centering Ability and Influence of Experience When Using WaveOne Single-File Technique in Simulated Canals - Mathieu Goldberg; Sandrine Dahan; Pierre Machtou (International Journal of Dentistry)
Introduction. WaveOne is a single endodontic instrument that reciprocates with a dedicated motor to shape root canal systems. The present study assessed the centering ability of this simplified protocol along with the effect of experience in simulated plastic canals. Methods. One experienced operator shaped two groups of simulated canals. Groups 1 and 3 each comprised 30 blinded L-shaped canals or S-shaped canals, respectively. Photographs were taken before and after shaping and digitally assessed centering after superimposition of the pictures. Time of shaping, number of passes, canal aberrations, and instrument degradation were recorded. In group 2 shaping was done on 30 blinded L-shaped canals by 30 different students with no prior experience with WaveOne. Results. All three groups yielded satisfactory, reproducible shaping. Centering ratios were low and homogeneous in all groups, with no significant differences between the experienced operator and the students. Apical transportation values were very low (≤0.138 mm) with no instances of blockage or separation. The average shaping time was short (43 to 101,6 sec). Conclusions. Within the limits of the study, the WaveOne instrument had excellent centering ability with a low risk of fracture or blockage and a short shaping time, regardless of the operator’s level of experience.